Informing the Plastic Treaty negotiations on science - experiences from the Scientists’ Coalition for an Effective Plastic Treaty - Syberg, Kristian (2024)
The ongoing international negotiations on a global plastics treaty will have pivotal implications for future efforts to transform the plastic economy. This is essential since the current use of plastic in the economy impacts the environment beyond the planetary carrying capacity. To ensure that the forthcoming Treaty can provide the foundation for this transition, the best available science must be made available in the negotiations, but with no formal scientific mechanism to inform the negotiations process, this is not ensured. The Scientists’ Coalition for an Effective Plastic Treaty serves as an example of how the global scientific community has self-organized and come together to address this task, working with five different categories of science-policy communication. The Scientists’ Coalition’s work is made transparent here with the hope that it can inspire organization of scientific input into other future policy areas.